Impact-Crush Separation Characteristics of Coal and Gangue. Issue 3 (3rd April 2018) - Yang, Daolong; Li, Jianping; Zheng, Kehong; Du, Changlong; Liu, Songyong
ABSTRACT: Utilizing the difference in hardness, coal and gangue can be separated by the impact-crush technology for utilization underground. The influence of hardness and impact velocity on the crush-ratio difference of coal and gangue was studied using an impact-crush separator and was optimized using the orthogonal experiment method. The equation of the impact-crush separation characteristics of coal and gangue was obtained by means of a regression analysis of the experiment results. The results indicated that the crush-ratio difference of coal and gangue had a linear relationship with the hardness and impact velocity of coal and gangue. It decreased with an increase of coal hardness and increased with an increase of gangue hardness. Coal hardness had a remarkable influence on the crush-ratio difference of coal and gangue; the gangue hardness and the impact velocity had the least effect.